Psychosocial Aspects of Adult Acne: Data from 13 European Countries - Ilknur K. Altunay; Ezgi Özkur; Florence J. Dalgard; Uwe Gieler; Lucía Tomas Aragones; Lars Lien; Françoise Poot; Gregor B. Jemec; Laurent Misery; Csanád Szabó; Dennis Linder; Francesca Sampogna; et al. (Medical Journals Sweden, 2020)
The link between acne and psychiatric morbidities has been demonstrated in many studies; however, large scale studies aiming to reveal the psychosocial impact of acne are rare. The aim of this study was to assess the psychological burden of adult acne patients. This analysis was based on a multicenter study including 213 acne patients and 213 controls from 13 European countries. The Hospital Anxiety and Depression Scale (HADS), Dermatology Life Quality Index, and EuroQol 5 dimensions 3 levels scores of the patients with acne were analyzed. Patients with acne (n = 213) had higher HADS scores for anxiety (mean ± standard deviation 6.70 ± 3.84) and depression (3.91 ± 3.43) than the controls (p < 0.001 for both). For patients with acne, 40.6% reported that they were very concerned about their skin disease, 12.3% had suicidal ideation, and, among those, 10 (4%) patients implied that acne was the cause of their suicidal thoughts. After adjusting for other variables, patients who had suicidal ideation (p = 0.007, and adjusted odds ratio 3.32 [95% confidence interval (CI): 1.39-7.93]) and stressful life events (p < 0.001, and adjusted OR 5.85 [95% CI: 2.65-12.86]) had a greater chance of fulfilling the HADS criteria for anxiety. This study highlights the need for a psychotherapeutic approach in order to recognize the concerns of acne patients and optimize their treatment.